2009
DOI: 10.1016/j.jneuroim.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of the in vitro effects of BDE-47 on innate immune responses in children with autism spectrum disorders

Abstract: Autism spectrum disorders (ASD) are complex neurodevelopmental disorders that manifest in childhood. Immune dysregulation and autoimmune reactivity may contribute to the etiology of ASD and are likely the result of both genetic and environmental susceptibilities. A common environmental contaminant, 2,2′,4,4′-tetrabrominated biphenyl (BDE-47), was tested for differential effects on the immune response of Peripheral blood mononuclear cells (PBMC) isolated from children with ASD (n=19) and age-matched typically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 57 publications
0
51
1
Order By: Relevance
“…Dissecting ASD heterogeneity and taking into account the various co-morbidities should be the primary focus of investigations in the immediate future. It will also be essential to obtain a better understanding 3 , 0 , 0 ↔ 2, same author (Jyonouchi et al, 2011(Jyonouchi et al, , 2012) GM-CSF 1 , 1 , 2 ↔ 2, same author ) IFNγ 4 , 3 , 4 ↔ 7 ((Jyonouchi et al, 2001, 2002Molloy et al, 2006;Ashwood et al, 2011) IL-10 2 , 11 , 7 ↔ 7 (Jyonouchi et al, 2001Molloy et al, 2006;Ashwood et al, 2011) IL-12 4 , 6 , 4 ↔ 4 (Jyonouchi et al, 2005 3 , 0 , 5 ↔ 5 (Jyonouchi et al, 2001(Jyonouchi et al, , 2002(Jyonouchi et al, , 2011Molloy et al, 2006;Ashwood et al, 2011) IL-6 3 , 9 , 2 ↔ 6 (Jyonouchi et al, 2001Ashwood et al, 2009Ashwood et al, , 2011 Measles antibody 0 , 0 , 2 ↔ 2 ( D ' Souza et al, 2006;Baird et al, 2008) sTNFRII 5 , 3 , 0 ↔ 3, same author (Jyonouchi et al, 2001(Jyonouchi et al, , 2005(Jyonouchi et al, , 2008) TNF-α 14 , 4 , 2 ↔ 7 (Jyonouchi et al, 2001(Jyonouchi et al, , 2002(Jyonouchi et al, , 2005(Jyonouchi et al, , 2011(Jyonouchi et al, , 2012Ashwood et al, 2009Ashwood et al, , 2011 of the underlying causes of the disease by investigating possible effects on synapse formation, myelination or hormonal biogenesis and secretion in the context of different ASDs. Biomarker profiling studies in plasma and serum have already established that there are effects on hormones and growth factors involved in regulation of whole-body metabolism and immune function in ASD, with potential gender-related effects …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissecting ASD heterogeneity and taking into account the various co-morbidities should be the primary focus of investigations in the immediate future. It will also be essential to obtain a better understanding 3 , 0 , 0 ↔ 2, same author (Jyonouchi et al, 2011(Jyonouchi et al, , 2012) GM-CSF 1 , 1 , 2 ↔ 2, same author ) IFNγ 4 , 3 , 4 ↔ 7 ((Jyonouchi et al, 2001, 2002Molloy et al, 2006;Ashwood et al, 2011) IL-10 2 , 11 , 7 ↔ 7 (Jyonouchi et al, 2001Molloy et al, 2006;Ashwood et al, 2011) IL-12 4 , 6 , 4 ↔ 4 (Jyonouchi et al, 2005 3 , 0 , 5 ↔ 5 (Jyonouchi et al, 2001(Jyonouchi et al, , 2002(Jyonouchi et al, , 2011Molloy et al, 2006;Ashwood et al, 2011) IL-6 3 , 9 , 2 ↔ 6 (Jyonouchi et al, 2001Ashwood et al, 2009Ashwood et al, , 2011 Measles antibody 0 , 0 , 2 ↔ 2 ( D ' Souza et al, 2006;Baird et al, 2008) sTNFRII 5 , 3 , 0 ↔ 3, same author (Jyonouchi et al, 2001(Jyonouchi et al, , 2005(Jyonouchi et al, , 2008) TNF-α 14 , 4 , 2 ↔ 7 (Jyonouchi et al, 2001(Jyonouchi et al, , 2002(Jyonouchi et al, , 2005(Jyonouchi et al, , 2011(Jyonouchi et al, , 2012Ashwood et al, 2009Ashwood et al, , 2011 of the underlying causes of the disease by investigating possible effects on synapse formation, myelination or hormonal biogenesis and secretion in the context of different ASDs. Biomarker profiling studies in plasma and serum have already established that there are effects on hormones and growth factors involved in regulation of whole-body metabolism and immune function in ASD, with potential gender-related effects …”
Section: Discussionmentioning
confidence: 99%
“…This also makes them potentially useful as models for drug discovery. Several studies have now used PBMCs to investigate the pathology underlying ASD, mainly concerning immunological responses (Jyonouchi et al, 2001(Jyonouchi et al, , 2002(Jyonouchi et al, , 2005(Jyonouchi et al, , 2008(Jyonouchi et al, , 2011(Jyonouchi et al, , 2012Molloy et al, 2006;Ashwood et al, 2009Ashwood et al, , 2011Onore et al, 2009;Rose et al, 2012b;Siniscalco et al, 2012), measles virus reaction (Kawashima et al, 2000;D'Souza et al, 2006;Baird et al, 2008) and β-endorphin levels (Brambilla et al, 1997;Cazzullo et al, 1999). The main difference in ASD PBMCs compared to control PBMCs have been identified as altered levels of cytokines and inflammation-related factors such as CCL7 (Jyonouchi et al, 2011(Jyonouchi et al, , 2012, TNF-α (Jyonouchi et al, 2001(Jyonouchi et al, , 2002(Jyonouchi et al, , 2005(Jyonouchi et al, , 2011(Jyonouchi et al, , 2012Ashwood et al, 2009Ashwood et al, , 2011), IL-10 (Jyonouchi et al, 2001(Jyonouchi et al, , 2002(Jyonouchi et al, , 2005(Jyonouchi et al, , 2011(Jyonouchi et al, , 2012Molloy et al, 2006;Ashwood et al, 2011), IL-1β (Jyonouchi et al, 2001(Jyonouchi et al, , 2005(Jyonouchi...…”
Section: Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%
“…96,103 In fact, Braunschweig et al found a significant correlation between maternal IgG reactivity to fetal brain proteins and a childhood diagnosis of autism. 104 Altogether, the evidence suggests that environmentally driven peripheral immune dysfunctions and associated neuropathological consequences form a series of interlinked events, which can manifest in autistic features.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…94,95 Inflammatory cytokine alterations in subjects prone to environmental risks have been evident in several studies, 79,93,96 and it is plausible that increased neuroinflammation provoked by elevated cytokines could contribute to observed behavioural dysfunction in autistic individuals.…”
mentioning
confidence: 99%
“…We have come to recognize that the extremely low rate of escape of POPs from the reservoir, which is nested within the reservoir or stock of materials and products, is a source of concern because it could result in exposures that could cause subtle toxicological effects in humans and biota (Boucher et al, 2009;Ashwood et al, 2009;Fernie et al, 2008Fernie et al, , 2009.…”
Section: Conceptual Model Of Popsmentioning
confidence: 99%